Key digital health literacy competencies for citizens – A Delphi study - Mika Uitto; Merja Hoffrèn-Mikkola; Leena Paakkari (Digital Health, 2025)
Objective Digital technologies provide citizens with many opportunities to increase control over and improve health, but their use requires digital health literacy. This study aimed to identify the most important competencies that citizens will need over the next 3 years to promote and maintain good health and wellbeing through digital technology. Methods Using a three-round Delphi method, Finnish experts on digital health ( n  = 29) listed competencies needed by citizens over the next 3 years to promote and maintain their health and wellbeing through digital technology and then evaluated and ranked them based on their perceived importance. Qualitative and quantitative methods were used to analyse the data. Results A broad list of competencies was produced, and the 17 most important were identified. The two most important competencies were the ability to use electronic identification and general IT proficiency. Conclusion The findings suggest that being digitally health literate in the modern world goes beyond the ability to seek, assess, understand, and apply online health information. It also encompasses electronic identification, general IT proficiency, navigating and using digital health services, accessing personal health records, and ensuring online privacy and security. These results offer important insights into the competencies needed to meet current digital health challenges, with implications for both assessment tools and intervention strategies.